Presaturated iron‐core fault current limiters for MVDC power system applications - Ibrahim A. Metwally; Mohamed Eladawy (IET Electric Power Applications)
Abstract This paper presents design and dynamic performance investigation of a 25kV full‐scale, modular topology (arranged on the sides of a regular hexagon), medium voltage direct current (MVDC) permanent magnet (PM) biased presaturated fault current limiter (PMFCL). This PMFCL represents a cost‐effective design with enhanced longevity, reliability, scalability, and controllability. The scalability of this modular design can be extended by adding or removing CI (letters: CI) core units for different power system applications in a voltage range from 5 to 50kV or more. The rated steady‐state (DC) and fault currents of 1kA and 4kA, respectively. The detection free and self‐triggering performance of this PMFCL is designed and simulated through a 3D coupled model of electric‐circuit magnetic‐field of COMSOL Multiphysics. Accurate representation of PM behaviour, especially in the second quadrant of its B−H hysteresis loop of Jiles‐Atherton method gives realistic performance of the PMFCL. Comprehensive finite element simulations are carried out to study the effect of design parameters on the dynamic performance of PMFCL. Good agreement is found between COMSOL simulation results of DC‐biased PFCL and experimental results of a developed small‐scale prototype. Results reveal that the MVDC PMFCL shows significant improvement and satisfactory performance, in terms of fault current clipping ratio, fault current slope, and power losses, as compared to the conventional MVDC DC‐biased presaturated CI iron‐core fault current limiter (PFCL).